A Thin-Film Thermal Meta-Device With Dual Function of Thermal Shield and Generation Based on an Artificially Tilted Structure - Zhang, Qingqing; Yuan, Junyu; Zhu, Wei; Deng, Yuan (Frontiers in Physics, 2022)
A thin-film thermal meta-device with dual-function of thermal shield and generation is proposed and fabricated in this work. The tilted layered structure composed of thermoelectric materials with low thermal conductivity and metal materials with high thermal conductivity is designed to realize the orientation of incident heat flux and utilization of heat energy based on the Seebeck effect of the materials. The constructed transverse thin-film thermoelectric device with Bi2Te3/Cu layered structure can achieve a maximum output voltage of 20.4 mV and a maximum output power of 7.39 μW at a temperature difference of 80 K. On this basis, the dual-functional film meta-device based on transformation thermodynamics is capable of realizing a heat flux shielding in the central area and generating a transverse output voltage. The experimental results also indicate that there exists a well linear relationship between the output voltage of the meta-device and the temperature difference, which can be extended to accurately monitor the temperature of the central area. This work provides a certain reference for the development of a new class of thermoelectric devices with thermal protection and temperature detection capability.